Tahfiz House and Social Formation: Quranic Education, Agency, and Socio-Political Dynamics - Ahyar Rasyidi; Jailani Jailani (SYAMIL: Journal of Islamic Education, 2024)
This article explores the formation of social formations influenced by the growth and dynamics of Qur'anic education through the existence of Rumah Tahfiz. This model of Qur'anic education is considered revolutionary compared to previous approaches because it brings various innovations in education that are more in line with the needs of urban Muslim communities as its main target. The core question of this article is: How does the presence of Rumah Tahfiz affect social formations in the city of Banjarmasin? Through an ethnographic approach, including participatory observation for three months from September to November 2023, this article finds that social dynamics and formations have changed the face of Rumah Tahfiz as an institution of Qur'anic education, while also emphasizing the role of Rumah Tahfiz in changing the social structure of the surrounding community.